Determinants of female time allocation in selected districts of rural Pakistan - Malik, Sohail; Nazli, Hina; Sultana, Nargis (Pakistan Institute of Development Economics, 1994)
This paper attempts to explain female time allocation for rural women in selected districts of Pakistan. This topic is of considerable importance for several reasons. At an academic leveL the fact that the female labour force participation decision and the hours worked are jointly determined raises interesting problems of modelling and econometric estimation in taking account of the selectivity bias thus introduced into OLS estimation. At the policy level, an insight into the factors influencing female labour force participation is extremely important in a developing country such as Pakistan where the majority of females do not participate in mainstream economic activities. The objective of this study is to determine the factors affecting the optimum time allocation between market and housework of females in rural Pakistan. In a male dominated society like Pakistan with strong cultural taboos, a woman's labour force participation can be expected to depend significantly on non-market factors. In this study we examine, in particular, whether women's decisions not to work outside the home are influenced more by social norms, for example purdah and patriarchy, or by economic constraints such as lack of relevant education and training, non-availability of job opportunities and low wages etc.